“Takes longer to reach your goals” Experiences before and after parental leave in the geothermal industry - Sara Matthíasdóttir 1989- (2019)
This study explores how employees experience returning from parental leave when working in a geothermal industry in Iceland and New Zealand. The study is conducted using qualitative research methods, where data was collected from ten interviews, five were from Iceland and five from New Zealand, all working in geothermal industry, who have had a baby within three years before the interview and have taken a parental leave. Most of the interviewees are in a global network called WING (Women in Geothermal), a group of determined individuals that want to promote and help women to advance in the geothermal industry. The research examines the experience of taking a parental leave when the focus is on the career, the barriers parents face, how the people in the industry tackle work and home-life obstacles, and how they meet their responsibilities at work. The major themes recurring throughout the interviews were: absence from work when taking a parental leave, flexibility at work, part-time work, and support from their employer.